Upaya Meningkatkan Hasil Belajar IPS dengan Menggunakan Model PAIKEM berbantuan Media Power Point pada Peserta Didik Kelas VIII-8 SMP Negeri 1 Palangka Raya - Khairunnisa Khairunnisa; Chandra Anugrah Putra (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This study aims to determine the increase in social studies learning outcomes and learning activities of students by applying the PAIKEM Model assisted by Media PowerPoint. The method used in this study was to use the Classroom Action Research (CAR) design. The subjects in this study amounted to 38 students, for data collection techniques used were observation and tests. This study uses qualitative and quantitative data analysis. The results of the study show that the activity is good and learning outcomes increase. This can be seen in the first cycle of student learning activities obtained 3.19 with good categories while in the second cycle obtained 3.78 with good categories. Increased learning outcomes in the first cycle of the average value of students are 70 with classical completeness 60.52% and in the second cycle, the average value of students is 84 with classical completeness to 89.47%. It can be concluded that there is an increase in learning outcomes using the PAIKEM model assisted by Media PowerPoint.